Water Purification from Ions of Cadmium (II) Using a Bio-Plateau - Lapan, Oksana; Mikhyeyev, Oleksandr; Madzhd, Svitlana; Dmytrukha, Tetyana; Cherniak, Larysa; Petrusenko, Valentyna (My University, 2019)
The study was conducted with the purpose of experimentally developing the method of water purification from ions of cadmium (II) using a new design of a bio-plateau, which is based on the use of terrestrial plants. In order to construct the bio–plateau, the following chemically inert floating materials were used as the substrate: perlite, expanded clay, granular foam, vermiculite, cork, on top of which the seeds of higher terrestrial plants were placed. The experimental data showed that foam was the best of the tested substrates, and of plants – barley, oats, corn and rye. The constructed bio-plateau was placed into tanks with a solution of cadmium on the 9th day of incubation to study the cleaning efficiency of terrestrial plants on the aquatic environment. Determination of the residual concentration of cadmium was performed with the method of AAC at λ=228.8. As a result, it was found that rye showed the best sorption properties of the tested plants. The influence of additional aeration and pH of the medium on the degree of water purification was established. The highest treatment efficiency was observed in the variant of a bio-plateau with aeration and at a pH of 8–9. The study shows the possibility of using terrestrial plants for the phytoremediation of water bodies

Дослідження проводились з метою експериментальної розробки методу очищення води від іонів кадмію (II) за новою конструкцією біоплато, яка базується на використанні наземних рослин. Для побудови біоплато в якості субстрату використовували такі хімічно інертні плаваючі матеріали: перліт, керамзит, пінопласт, вермикуліт, пробку, поверх яких поміщали насіння вищих наземних рослин. Експериментальні дані показали, що з досліджуваних субстратів найкраще пінопласт, а з рослин – ячмінь, овес, кукурудза та жито. Сконструйоване біоплато поміщали в резервуари з розчином кадмію на 9 добу інкубації для вивчення ефективності очищення наземних рослин від водного середовища. Визначення залишкової концентрації кадмію проводили методом ААС при λ=228,8. В результаті встановлено, що найкращі сорбційні властивості серед досліджуваних рослин показало жито. Встановлено вплив додаткової аерації та рН середовища на ступінь очищення води. Найбільшу ефективність обробки спостерігали у варіанті біоплато з аерацією та рН 8–9. Дослідження показує можливість використання наземних рослин для фіторемедіації водойм
Keywords: phytoremediation; bio-plateau; terrestrial plants; cadmium (II); фіторемедіація; біоплато; наземні рослини; кадмій (ІІІ); кафедра екології та екоменеджменту